Biofilm Formation by Staphylococcus aureus Isolated from Food Contact Surfaces in the Dairy Industry of Jalisco, Mexico - María-Guadalupe Avila-Novoa; Maricarmen Iñíguez-Moreno; Oscar-Alberto Solís-Velázquez; Jean-Pierre González-Gómez; Pedro-Javier Guerrero-Medina; Melesio Gutiérrez-Lomelí (Journal of Food Quality)
Staphylococcus aureus is an important food-borne pathogen able to form biofilms. This pathogen is responsible for outbreaks of food-borne illnesses associated with the consumption of milk and dairy products. The aim of this study was to evaluate the biofilm-forming ability of S. aureus isolates, recovered from food contact surfaces in the dairy industry of Jalisco, Mexico. A total of 84 S. aureus strains were evaluated. The isolates were characterized phenotypically by culture on Congo red agar plates. The ability of the strains to form biofilms was investigated in 96-well flat-bottomed microtiter polystyrene plates. Stainless-steel coupons were used as an experimental surface. Biofilm formation was observed, using epifluorescence microscopy and scanning electron microscopy. Detection of the icaADBC genes in S. aureus was performed by the PCR technique. A total of 52.3% (44/84) of the S. aureus strains contained the icaADBC gene that synthesizes polysaccharide intercellular adhesion (PIA) molecules. On Congo red agar, 75% (63/84) of the S. aureus isolates were biofilm producers, 16.6% (14/84) were non-biofilm formers, and 8.3% (7/84) showed a noncharacteristic phenotype. The biofilm production of the S. aureus strains SA-4E, SA-9, SA-13, and SA-19 on stainless-steel coupons was investigated at 25°C for 8 days, and the detected cell population density was approximately 7.15–7.82 log CFU cm−2. In addition to the ability of biofilm production, it is important to highlight that these strains are potential enterotoxin producers as se genes have been previously detected in their genomes. A part of the ability of biofilm production and the determination of the presence of virulence determinants in the genome of S. aureus can contribute to the pathogenicity of strains. Therefore, vigilant food safety practices need to be implemented in the dairy industries regarding FCS to prevent food-borne infections and intoxications due to S. aureus contamination.